Probabilistic Fatigue Crack Initiation and Propagation Fields Using the Strain Energy Density - Correia, J.A.F.O.; Huffman, P.J.; De Jesus, A.M.P.; Lesiuk, G.; Castro, J.M.; Calcada, R.A.B.; Berto, F. (Проблемы прочности, 2018)
Recently, Huffman developed a strain energy density based on Walker-like stress life and fatigue crack growth behavior. In this paper, the Huffman model based on local strain energy density is used to predict the fatigue crack initiation and propagation for the P355NL1 pressure vessel steel. This model is combined with the generalized probabilistic fatigue model proposed by Correia aiming the generation of probabilistic fatigue crack initiation and propagation fields. In this study, the local stress and strains at the crack tip were obtained combining linear-elastic and elastoplastic analyses. The probabilistic fatigue crack growth rates fields for several stress R-ratios are estimated considering strain, SWT and equivalent stress amplitude damage parameters. A comparison between the experimental fatigue crack growth (FCG) data and the generated probabilistic FCG fields is made with very satisfactory correlations being found. В настоящее время Хаффман разработал концепцию плотности энергии деформации, основанную на циклической долговечности и развитии усталостной трещины по типу Волкера. Модель Хаффмана, базирующаяся на локальной плотности деформации, используется для прогнозирования инициирования и распространения усталостной трещины в стали P355NL1, применяемой в сосудах высокого давления. Данная модель сочетается с обобщенной вероятностной моделью усталости, ранее предложенной одним из соавторов, суть которой состоит в генерации вероятностных полей инициирования и распространения усталостных трещин. Получены локальные напряжения и деформации в вершине трещины, объединяющие их линейно-упругие и упругопластические составляющие. Для нескольких значений коэффициента асимметрии цикла напряжений R оценены вероятностные поля скоростей роста усталостных трещин с учетом параметров повреждения, параметра Смита–Ватсона–Топпера (SWT) и эквивалентных параметров амплитуды напряжения. Сравнение экспериментальных данных по приращению усталостной трещины с прогнозируемыми вероятностными полями ее роста показывает их тесную корреляцию. На сьогодні Хаффман розробив концепцію густини енергії деформації на основі циклічної довговічності і поширення тріщини від утомленості по типу Волкера. Модель Хаффмана, що базується на локальній густині енергії деформації, використовується для прогнозування ініціювання і поширення тріщини від утомленості в сталі P355NL1, яка використовується для виготовлення посудин високого тиску. Дана модель поєднується з узагальненою імовірнісною моделлю утоми, раніше запропонованою одним із співавторів, суть якої полягає в генерації імовірнісних полів ініціювання і поширення тріщин від утомленості. Отримано локальні напруження і деформації у вершині тріщини, що об’єднують їх лінійно-пружні і пружнопластичні складові. Для декількох значень коефіцієнта асиметрії циклу напружень R оцінено імовірнісні поля швидкостей росту тріщин від утомленості з урахуванням параметрів пошкодження, параметра Сміта–Ватсона–Топпера (SWT) й еквівалентних параметрів амплітуди напруження. Порівняння експериментальних даних щодо приросту тріщини від утомленості з прогнозованими імовірнісними полями її росту свідчить про їх тісну кореляцію.